Development of a Data Analysis Tool for the EDEN ISS Project - BRYSON, Christopher (Luleå tekniska universitet, Rymdteknik, 2022)
The EDEN ISS project, initiated by the German Aerospace Center (DLR) focuses on the development of greenhouses for future Space habitats on the Moon and Mars. For this, they run a full-size experiment in Antarctica in collaboration with NASA. This experiment is remotely controlled and monitored by the mission control team in Bremen, Germany. The aim of this thesis is to improve the accessibility of the data being pulled from the greenhouse in Antarctica and delivered to the mission control room. Furthermore, it promises to provide the EDEN ISS team with a set of tools to quickly and easily analyze historical data from the numerous sensors and devices currently installed inside the greenhouse module. To accomplish this, the development of a Data Analysis Tool was designed and programmed in Python, which generates accurate graphs and plots in a fast and user-friendly manner. This tool provides the user with a Graphical User Interface (GUI) which includes a set of easy-to-use tools to modify and manipulate the available data throughout the entire experiment’s lifetime, covering the years from 2018 to 2021. By using this tool, the EDEN ISS team can access relevant data and reach informed conclusions regarding the functionality and stability of the greenhouse experiment module in Antarctica.